Taṭwīr Kitāb “Matan al-Binā Wa al-Asās” Bi Waraqah al-`Amal (Student Work Sheet) `Alā Bāb aṡ-Ṡulāṡī al-Mujarrad Wa aṡ-Ṡulāṡī al-Mazīd Fī al-Faṣl aṡ-Ṡānī Bi Ma`had at-Taqlīdī Rauḍah al-Ḥikmah al-Waliyah Pango Raya Banda Aceh - Fadhil Fadhil; Mukhlisah Mukhlisah (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2020)
The problem in this study is that student are not able to apply the sharf method to identify fa fi'il and a'in fi'il and lam fi'il in this chapter of the mujarrad and ts ulasi mazid and are also unable to identify a additional letters in the tsulasi mazid chapter and author of the book is not put a distinguishing mark between the original letters and the additional letter in tsulasi mazid chapter. The purpose of this study is to find out the steps for developing and affectiveness of the product development of the book matan bina wal asas with LKS. The population and sampel of this study were all santri in class 2 in dayah raudhatuk hikmah al-waliyah in 2018/2019 totaling 57 people. The method used to select samples is a random method. A sample is 30 people. To collect research data using the following tools: Observasion, interviews, questionnaires and T test. As for analyzing the data researchers used qualitative and quantitative methods. The result of the study are the analysis of needs, and problem, collecting data, designing product, revising the product, testing the first product, revising the product, testing the second product, the final revision, and the final product. The product effectiveness of the development of the book matan bina wal asas with LKS in the chapter tsulasi mujarrad and stulasi mazid in raudhatul hikmah traditional al-waliyah Pango Raya is a researcher doing statiscal calculation whether or not the LKS media are effective? The result of the study show thar the T-count is -9,632 which is smaller than the T-table which is 2,048. So, therefore, accept H0 and reject Ha. Based on the calculation above it can be concluded that the LKS media is effective in learning sharf science